"Humanized torture" Code Constitutio Criminalis Theresiana - Feješ, Ištvan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
The work is divided into four major parts. In the first, introductory part, the author deals with the theoretical basis, the main rules and the role of torture in criminal proceedings inquisitorial type. In the second, the central part of the paper, the author presents the full text of all 32 members of the head 38 of the Code containing provisions on torture in Serbian translation with brief comments. The third part is dedicated to the abolition of torture in the Habsburg Monarchy 1776, after only eight years of the publication of the Code and the difficulties in implementing that decision. The fourth part is the conclusion, in which the author points out that the code can be criticized because of the legacy of the medieval spirit, but at the time of publication, but mostly because torture.Međutim, unlike their predecessors, providing for the unlimited brutal violence against suspected Code contains numerous provisions that protected the suspect and torture gave a milder, "humane" form.